2012
DOI: 10.1186/1475-2840-11-114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of weight loss and insulin reduction on arterial stiffness in the SAVE trial

Abstract: BackgroundChronic arterial stiffness contributes to the negative health effects of obesity and insulin resistance, which include hypertension, stroke, and increased cardiovascular and all-cause mortality. Weight loss and improved insulin sensitivity are individually associated with improved central arterial stiffness; however, their combined effects on arterial stiffness are poorly understood. The purpose of this study was to determine how insulin levels modify the improvements in arterial stiffness seen with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 31 publications
2
47
0
3
Order By: Relevance
“…26 Accordingly, baPWV and cfPWV are correlated similarly with cardiovascular disease risk factors and clinical events. 27 We have reported stronger associations of coronary artery calcification 28 and weight loss/insulin reductions 20 with baPWV than cfPWV. In the present study and others, 20 cfPWV had twice the variance of baPWV, which could explain the lack of association between cfPWV and Ab status; however, it does not explain why cfPWV was more strongly related with WMHv.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…26 Accordingly, baPWV and cfPWV are correlated similarly with cardiovascular disease risk factors and clinical events. 27 We have reported stronger associations of coronary artery calcification 28 and weight loss/insulin reductions 20 with baPWV than cfPWV. In the present study and others, 20 cfPWV had twice the variance of baPWV, which could explain the lack of association between cfPWV and Ab status; however, it does not explain why cfPWV was more strongly related with WMHv.…”
Section: Resultsmentioning
confidence: 83%
“…27 We have reported stronger associations of coronary artery calcification 28 and weight loss/insulin reductions 20 with baPWV than cfPWV. In the present study and others, 20 cfPWV had twice the variance of baPWV, which could explain the lack of association between cfPWV and Ab status; however, it does not explain why cfPWV was more strongly related with WMHv. Measures of central stiffness may simply be associated more strongly with cardiovascular disease risk and cerebrovascular disease, while baPWV may represent another phenomenon linking systemic vascular stiffness with Ab deposition in the brain.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Dengo et al in a recent randomized, placebo-controlled study proved that weight loss through a hypocaloric diet can reduce arterial stiffness in major arteries in older patients [16]. Hughes et al demonstrated that young overweight and obese adults who lower their insulin levels and lose weight over 6 months experience decreased vascular stiffness measured by pulse wave velocity (PWV) [17].…”
Section: Discussionmentioning
confidence: 99%